CADM1 associates with Hippo pathway core kinases; membranous co–expression of CADM1 and LATS2 in lung tumors predicts good prognosis. Issue 7 (29th May 2019) - Ito, Takeshi; Nakamura, Atsuko; Tanaka, Ichidai; Tsuboi, Yumi; Morikawa, Teppei; Nakajima, Jun; Takai, Daiya; Fukayama, Masashi; Sekido, Yoshitaka; Niki, Toshiro; Matsubara, Daisuke; Murakami, Yoshinori
Abstract: Cell adhesion molecule‐1 (CADM1) is a member of the immunoglobulin superfamily that functions as a tumor suppressor of lung tumors. We herein demonstrated that CADM1 interacts with Hippo pathway core kinases and enhances the phosphorylation of YAP1, and also that the membranous co–expression of CADM1 and LATS2 predicts a favorable prognosis in lung adenocarcinoma. CADM1 significantly repressed the saturation density elevated by YAP1 overexpression in NIH3T3 cells. CADM1 significantly promoted YAP1 phosphorylation on Ser 127 and downregulated YAP1 target gene expression at confluency in lung adenocarcinoma cell lines. Moreover, CADM1 was co–precipitated with multiple Hippo pathway components, including the core kinases MST1/2 and LATS1/2, suggesting the involvement of CADM1 in the regulation of the Hippo pathway through cell‐cell contact. An immunohistochemical analysis of primary lung adenocarcinomas (n = 145) revealed that the histologically low‐grade subtype frequently showed the membranous co–expression of CADM1 (20/22, 91% of low‐grade; 61/91, 67% of intermediate grade; and 13/32, 41% of high‐grade subtypes; P  < 0.0001) and LATS2 (22/22, 100% of low‐grade; 44/91, 48% of intermediate‐grade; and 1/32, 3% of high‐grade subtypes; P  < 0.0001). A subset analysis of disease‐free survival revealed that the membranous co–expression of CADM1 and LATS2 was a favorable prognosis factor (5‐year disease‐free survival rate: 83.8%), even with nuclear YAP1‐positive expression (5‐year disease‐free survival rate: 83.7%), whereas nuclear YAP1‐positive cases with the negative expression of CADM1 and LATS2 had a poorer prognosis (5‐year disease‐free survival rate: 33.3%). These results indicate that the relationship between CADM1 and Hippo pathway core kinases at the cell membrane is important for suppressing the oncogenic role of YAP1. Abstract : We herein demonstrated that CADM1 interacts with Hippo pathway core kinases and enhances the phosphorylation of YAP1, and also that the membranous co–expression of CADM1 and LATS2 predicts a favorable prognosis in lung adenocarcinoma.